In a long-winded road: Understanding the lived experiences of faculty members on module writing in the new normal - Roselle Matammu Soriano; Kristine Bernadette M. Apolonio; Carmela Gandia Blando (International Journal of Evaluation and Research in Education (IJERE), 2022)
The COVID-19 pandemic has caused unprecedented difficulties and obstacles for educational sectors, with no one knowing when it will end. The number of illnesses continued to rise while countries worldwide established plans and processes to limit the virus. To maintain and deliver a high-quality education notwithstanding community quarantine, the new normal should be incorporated into the formulation and implementation of the "new normal educational policy." Thus, this qualitative study sought to develop a deeper understanding of teachers' experiences in module writing. Specifically, it explored the challenges they experienced and identified the coping mechanisms they employed. A total of 15 participants were purposely selected who took part in an individual in-depth and semi-structured interview. The themes emerged as the challenges of the faculty members, namely: Insufficient training on module writing, lack of books & other resources, subjects are not in line with the field of specialization, overloaded number of subject preparations, and inadequate office supplies/equipment for reproduction of modules. Further, the themes on the coping mechanisms include collaboration with colleagues, self-motivation, proper time management, and initiative and resourcefulness. Hence, the faculty member's best practices and coping mechanisms to improve their teaching through module writing were indicators that they want to grow and embrace professional development. On the other hand, to address the identified problems, a proposed enhancement program will be initiated. The platform focused on Strengthening the “Campus’ Instructional Materials Development Program” and enhancing campus activities on developing instructional materials.